Modern approaches to Islamic family law reform: the quest for a balanced approach in the Malaysian context - Haneef, Sayed Sikandar Shah (IRAJ Research Forum, 2015)
Muslim women have been caught in a tag- of- war between the forces of preserving Muslim family identity and advocates of its reform along the line of gender equality and International human rights. Given the current socio-political milieu at the global arena, the horizons for this tension to evaporate seem dim anytime soon. Reacting to Western human rights criticism of Islamic family law, the conservative camp regard any attempt at reforming Islamic family law as a naked invasion of Western imperialism on Muslim personal domain. Reform proponents, on the other hand, indict conservative interpretation of Islamic family law as the primary cause of women oppression in Muslim societies. Accordingly, they constantly endeavour to lobby for reform of Muslim family law using either international bills of rights or gender equality as the framework. Consequently, Muslim women`s rights in the family has become a matter of paradoxical exegeses. To break this deadlock, this paper argues for a mediated solution by using critical content analysis of the two trends as a way forward for Shari`ah-based reform in Malaysia.